Primary leiomyosarcoma of bones – a rare entity in two different presentations - Duminda, Withanage Don; Samarathunga, Dishan Randika; Anupama, Appu Arachchige Gayani Harindi; Sooriyarachchi, Rukshan; Navarathna, Paththinikuttige Alexander Gamini; Rathnayaka, Rathnayaka Mudiyanselage Ananda Sarath; Liyanage, Rubasinha Liyanage Pemith Ranura; Malhasi, Ihala Wellala Gunawardena Arachchige Labandi (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Leiomyosarcomas (LMS) originate from smooth muscle cells. They are very rare malignant neoplasms. Bony Leiomyosarcoma is a variant of spindle cell sarcoma, primarily affecting long bones, predominantly the distal femur and the proximal tibia followed by craniofacial skeleton. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To describe clinical presentation and diagnostic approach of primary leiomyosarcoma of bones in two different patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the cases. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 1. A 64-year-old male with a fracture of left distal femur after a fall was investigated and found to have a pathological fracture. An open biopsy of the fracture site confirms leiomyosarcoma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case 2. A 58-year-old previously healthy female presented with a swelling on right side mandibular region. Orthopantomogram radiograph (OPG) of mandible and Cone beam CT (CBCT) mandible was taken initially and revealed a large area of bone destruction of the right side of the mandible associated with a soft tissue mass. Initial incisional biopsy made the diagnosis of spindle cell sarcoma followed by excisional biopsy, which confirms the diagnosis of moderately differentiated leiomyosarcoma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Primary leiomyosarcoma of bones is very rare. Imaging features are helpful in the evaluation of such conditions, but final diagnosis should be based on histopathologic and immunohistochemical features.